The renaissance of Rio Tinto’s former industrial assets in France: enablers for successful post-mining transitions - Latham, C; Lhuissier, D; Mignot, M; Solana, J (Mine Closure 2024: 17th International Conference on Mine Closure, 2024)
Mineral resources are finite and therefore mining and mineral processing are temporary land uses. As a result, asset closure planning must be underpinned by the future post-mining land use. Recently, the focus of mine closure has shifted from solely environmental considerations to encompass social and economic outcomes, driving increased interest in post-mining transitions. In many jurisdictions the pathway to relinquishment and realising post-mining opportunities remains unclear and challenging to achieve. This uncertainty is resulting in suboptimal outcomes for industry, government, communities and society. Through safe and responsible asset closure, Rio Tinto is working to deliver shared benefits for host communities, employees and investors; positive environmental, social and governance (ESG) outcomes; and innovative solutions that minimise long-term liabilities. Rio Tinto manages several legacy mining, processing and infrastructure assets in France, where the strong spirit of partnership between industry, community and government has resulted in transitions to successful post-mining land uses. Through case studies, this paper illustrates Rio Tinto’s experience of asset transition in France, lessons learnt and the key enablers.
Keywords: mine closure; post-mining land use; post-mining transition; repurpose; relinquishment; legacy management; legislative policy framework; France